PEMAHAMAN PENDIDIKAN PANCASILA DAN KESADARAN HUKUM SERTA IMPLEMENTASI ETNOPEDAGOGI BAGI PELAJAR DI PANGKALAN KERINCI PELALAWAN RIAU - Radini, Radini; Supentri, Supentri; Erlinda, Sri; Arianto, Jumili; Grosman, Kingkel P (Unri Conference Series: Community Engagement, 2024)
The importance of understanding Pancasila education and legal awareness in shaping the character of students in Indonesia. Pancasila education not only aims to teach the country's basic values, but also plays a role in building strong legal awareness among the younger generation. Through an ethnopedagogical approach, this article describes how integrating local culture in the learning process can increase the relevance of teaching materials and facilitate a deeper understanding of the rights and obligations as citizens. This research shows that by linking the principles of Pancasila and law to the local cultural context, students become better able to apply these values ​​in everyday life. In conclusion, the implementation of ethnopedagogy in Pancasila education and legal awareness is very important to create a young generation who not only understands, but also applies these values ​​in practice, thereby contributing positively to society and the nation.